Decreases in plasma glucose, corticosterone and cholesterol levels following longterm consumption of stabilized rice bran in Albino Wistar rats. (Journal of Basic and Applied Research in Biomedicine, 2022)
The present study was designed to investigate the effects of long term stabilized rice bran (SRB) rich diet consumption on neuroendocrine and behavioral responses in rats. Cubes of standard rodent diet were crushed and mixed with SRB in the ratio of 2:1 and 1:1(w/w) to prepare pellets of moderate and high amount of SRB rich diet respectively. Albino wistar rats randomly assigned as control, moderate and high amount of SRB groups were treated accordingly with the respective diet for 6 weeks. Weekly cumulative food intakes but not body weights were smaller in SRB rich diet treated during 1st to 5th week of treatment, which were normalized at the end of the treatment. Animals treated with high SRB rich diet exhibited a decrease in plasma glucose, corticosterone as well as cholesterol levels. Cholesterol levels were also decreased by moderate SRB rich diet. The results are discussed in context of antioxidant and antistress property of rice bran. It is suggested that presence of tocopherol, tocotrienol, γ-orynazol and other unsaponifiable compounds in rice bran may produce a reduction in the cholesterol and glucose levels. A decrease in corticosterone levels may be explained in terms of antistress effects of rice bran.